2009
DOI: 10.1089/ars.2008.2226
|View full text |Cite
|
Sign up to set email alerts
|

Apurinic/Apyrimidinic Endonuclease/Redox Effector Factor-1(APE/Ref-1): A Unique Target for the Prevention and Treatment of Human Melanoma

Abstract: Management of melanoma is a growing and challenging public health issue requiring novel and multidisciplinary approaches to achieve more efficient prevention and therapeutic benefits. The aim of this article is to show the critical role of APE/Ref-1 on melanomagenesis and progression. APE/Ref-1 serves as a redox-sensitive node of convergence of various signals as well as a DNA-repair enzyme, and its activation protects melanocytes and melanoma cells from chronic oxidative stress and promotes cell survival via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 119 publications
2
7
0
Order By: Relevance
“…It is also well documented that elevated APE/Ref-1 is associated with chemo-and radio-resistance in a number of cellular systems. Recently, this group also suggested that APE/Ref-1 is involved in the regulation of metastasis produced by melanoma cells [125]. These studies suggested that, as an adaptive response induced by APE/Ref-1, this transcription factor besides efficiently repairs oxidative DNA damage, also regulates redox-sensitive signaling such as AP-1 and NF-κB, which are involved in melanoma genesis.…”
Section: Redox Signaling In Melanomamentioning
confidence: 97%
“…It is also well documented that elevated APE/Ref-1 is associated with chemo-and radio-resistance in a number of cellular systems. Recently, this group also suggested that APE/Ref-1 is involved in the regulation of metastasis produced by melanoma cells [125]. These studies suggested that, as an adaptive response induced by APE/Ref-1, this transcription factor besides efficiently repairs oxidative DNA damage, also regulates redox-sensitive signaling such as AP-1 and NF-κB, which are involved in melanoma genesis.…”
Section: Redox Signaling In Melanomamentioning
confidence: 97%
“…APE1/Ref-1 has also been shown to be associated with tumor resistance to both ionizing radiation and chemotherapy [ 123 125 ]. Consequently, APE/Ref-1 has emerged as a promising therapeutic target for cancer treatment [ 115 , 120 , 126 ].…”
Section: Cancer Redox Adaptationmentioning
confidence: 99%
“…4 and 5). Four of the transcription factors that APE1 regulates (NF-κB, AP-1, Stat3 and HIF-1α [25, 37, 49, 50]) have been implicated in pancreatic cancer progression, resistance to therapy, and metastatic potential [51, 52]. A recent review indicates that those four transcription factors are key regulators of multiple signals in pancreatic cancer and provides strong evidence for investigating the effects of targeting transcription factors to kill pancreatic cancer cells [53].…”
Section: Ape1’s Varied Functionsmentioning
confidence: 99%